LOGICAL FALLACY DALAM NARASI MEDIA CNN INDONESIA ‘PEMERINTAHAN BONEKA DI ERA JOKOWI-JK’ - Dini Sri Istiningdias; Gili Argenti (Jurnal Akrab Juara, 2019)
This research aims to determine the causes of governance in the Jokowi-JK era called a puppet government; identify the types of Logical Fallacy contained in news of puppet governments in the Jokowi-JK era; and analyze the result impact from Logical Fallacy in the news of the puppet government in the Jokowi-JK era. The research method was conducted using qualitative descriptive method. Based on reports in the Indonesian CNN media that Jokowi-JK began to be imaged as a puppet government since the 2014 presidential election season. This is indicated when Megawati once called Jokowi a party official. The public is concerned that if the head of state got intervention from the interests of the bearer party, it will harm the interests of the Indonesian people. This causes the fallacy or fallacy on the type of fallacies of relevance. This type of fallacy is a misguided thought that occurs because the narration given is not directed to the real problem but is directed to the personal condition and personal characteristics of the person (the interlocutor) who are actually not relevant to the truth or error of the contents of the argument. After being observed and analyzed, the results of the study show that there are three types of Logical Fallacy identified in the online reporting of CNN Indonesia, namely the Argument against the Reason / Argument of Ad Hominem, The Appeal to the Populace Type, and the Missing The Point Type Ignoratio Elenchi). The impact that resulted from the three types of Logical Fallacy in the Indonesian CNN online coverage was the emergence of hoax reporting on puppet government which harmed Jokowi-JK in his role in running the government.